2022
DOI: 10.3389/fpls.2022.934195
|View full text |Cite
|
Sign up to set email alerts
|

FERONIA-like receptor 1-mediated calcium ion homeostasis is involved in the immune response

Abstract: Calcium (Ca2+) is the most abundant divalent cation in plants, and cellular levels of Ca2+, which functions as a nutrient and secondary messenger, play a critical role in plant immunity. In the present study, we found that FERONIA-like receptor 1 (FLR1) positively regulates Magnaporthe oryzae resistance and that expression of FLR1 is strongly induced in response to Ca2+ deficiency. In addition, the Ca content in the shoots of flr1 was lower than that in wild-type, and the M. oryzae-sensitive phenotype of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For instance, the respiratory burst oxidase homologs (RBOHs), that are involved in apoplastic ROS production, have been found to be regulated by FER and related proteins ( Franck et al., 2018 ; Zhang et al., 2020b ). FERONIA-like receptor 1 (FLR1) from rice is involved in the regulation of Ca2+ homeostasis in response to rice blast resistance ( Luo et al., 2022 ). However, it is currently unknown how the RALF–CrRLK1L complex regulates ROS production and interferes with calcium signaling during immune response ( Liao et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the respiratory burst oxidase homologs (RBOHs), that are involved in apoplastic ROS production, have been found to be regulated by FER and related proteins ( Franck et al., 2018 ; Zhang et al., 2020b ). FERONIA-like receptor 1 (FLR1) from rice is involved in the regulation of Ca2+ homeostasis in response to rice blast resistance ( Luo et al., 2022 ). However, it is currently unknown how the RALF–CrRLK1L complex regulates ROS production and interferes with calcium signaling during immune response ( Liao et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with quantitative disease resistance to Sclerotinia sclerotiorum in Arabidopsis (Derbyshire et al, 2019) and positively regulates defenses against the blast fungus Magnaporthe oryzae in rice (Hu et al, 2005). The RLPK Feronia is another multifunctional receptor monitoring cell wall integrity (Kohorn, 2015) and defenses against M. oryzae in response to Ca 2+ deficiency (Luo et al, 2022), but in tomato, it could facilitate fungal pathogenicity through mediating the Rapid Alkalinization Factor (RAFL)-FER pathway (Masachis et al, 2016). Both receptors in our pathosystem had a strong effect on treatment in the variancePartition analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the Arabidopsis mutant feronia ( fer ), the pollen tube fails to arrest and thus continues to grow inside the female gametophyte without rupture for the release of sperms [ 17 , 18 ]. Besides the role in reproduction, accumulating evidence suggests that FER plays critical roles in a diversity of biological processes, such as root growth [ 135 , 136 , 137 ], immune responses [ 21 , 138 , 139 , 140 , 141 , 142 ], environmental adaptations [ 143 , 144 , 145 , 146 ], etc.…”
Section: Cwi Signal Candidates In Fruit Ripeningmentioning
confidence: 99%
“…For example, a study by Gjetting SK et al [ 147 ] (2020) reported that RALF, the ligand of FER, could trigger signaling in Arabidopsis, and more recently, a study by Gao et al [ 148 ] (2022) demonstrated that FER signaling acts to trigger Ca 2+ signaling for pollen tube reception. Also, a study by Luo et al [ 141 ] (2022) reported that FER signaling could mediate calcium ion homeostasis implicated in the immune response. Importantly, Duan et al [ 126 ] (2020) demonstrated that FER is crucial for maintaining de-esterified pectin at the filiform apparatus, and pollen tube arrival at the ovule triggered the accumulation of nitric oxide at the filiform apparatus, whereby suppressing pollen tube attraction.…”
Section: Cwi Signal Candidates In Fruit Ripeningmentioning
confidence: 99%